The reality of food losses: A new measurement methodology - Delgado, Luciana; Schuster, Monica; Torero, Máximo (International Food Policy Research Institute, 2017)
Our objective is to improve how food loss is quantified and characterize the nature of food loss across the value chain for different commodities in a wide array of countries. For this purpose, we designed a set of surveys to measure the extent of food loss. While the surveys were tailored to specific countries and commodities and commodity varieties (for example, while Maize in Honduras and Guatemala have the same attributes, wheat in China has different attributes than wheat in Mexico), they provide a consistent measurement of food loss across different agents in the value chain (i.e., farmers, middlemen, and processors). The surveys capture detailed information about these agents’ different processes and quantify food loss along each production stage by collecting self-reported measures of the volumes and values of food losses incurred during different processes (harvesting, threshing, milling, shelling, winnowing, drying, packaging, transporting, sorting, picking, transforming, etc.). In addition, we estimate losses based on commodity damage by collecting detailed data from farmers, middlemen, and processors regarding the quality (based on damage coefficients) of agricultural commodities that they use as inputs and outputs. This allows us to quantify food loss in terms of the quality attributable to each agent across the value chain. Finally, we also estimate food loss based on commodity attributes by capturing information about different types of commodity attributes (e.g., size, impurities, broken grain, etc.) and ascertaining the price penalty that each of these types of crop damage entails. In this line, we are able to identify particular factors that diminish commodities’ values and thus are able to quantify food quality loss based on market conditions.